Does the composition of government expenditure matter for long-run GDP levels? - Richard, Kneller; Norman, Gemmell; Ismael, Sanz (Wiley, 2015)
We examine the long-run GDP impacts of changes in total government expenditure and in the shares of different spending categories for a sample of OECD countries since the 1970s, taking account of methods of financing expenditure changes and possible endogenous relationships. We provide more systematic empirical evidence than available hitherto for OECD countries, obtaining strong evidence that reallocating total spending towards infrastructure and education is positive for long-run output levels. Reallocating spending towards social welfare (and away from all other expenditure categories pro-rata) may be associated with modest negative effects on output in the long-run.